Can Education Compensate the Effect of Population Aging On Macroeconomic Performance? Evidence from Panel Data - Rainer Kotschy; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
This paper investigates the consequences of population aging and of changes in the education composition of the population for macroeconomic performance. Estimation results from a theoretically founded empirical framework show that aging as well as the education composition of the population influence economic performance. The estimates and simulations based on population projections and different counterfactual scenarios show that population aging will have a substantial negative consequence for macroeconomic performance in many countries in the years to come. The results also suggest that education expansions tend to offset the negative effects, but that the extent to which they compensate the aging effects differs vastly across countries. The simulations illustrate the heterogeneity in the effects of population aging on economic performance across countries, depending on their current age and education composition. The estimates provide a method to quantify the increase in education that is required to offset the negative consequences of population aging. Counterfactual changes in labor force participation and productivity required to neutralize aging are found to be substantial.
Keywords: J11; O47; 330; demographic change; demographic structure; distribution of skills; projections; education-aging-elasticity